An investigation of maximum experimental safety gap of CH4H2 blended fuel at different initial pressures. Issue 3 (31st December 2021) - Rui, Liu; Pan, Jun; Li, Ting; Wang, Qing Lu; Ma, Honghao; Shen, Wu Zhao
Abstract: The MESG (maximum experimental safety gap) of CH4 H2 mixtures were measured at different initial pressures (40–140 kPa). With an increase in hydrogen fraction, the classification of CH4 H2 mixtures was from Group IIA to Group IIC. The mixtures were classified as Group IIB when the hydrogen fraction was between 25% and 77%, followed by Group IIC with continuous increase in the amount of hydrogen. For calculating MESG of CH4 H2 blended fuel, the method based on oxygen amount is feasible at any initial pressure. It is different from Le Chatelier's equation, which is used to evaluate the low explosion limits for flammable mixtures but not suitable for calculating MESG. In this study, a formula calculating MESG‐based laminar flame velocity and initial pressure was proposed to obtain the MESG of CH4 H2 mixtures more easily.